Draft genome sequence of chickpea (Cicer arietinum) provides a resource for trait improvement - Varshney, Rajeev; Song, Chi; Saxena, Rachit; Azam, Sarwar; Yu, Sheng; Sharpe, Andrew; Cannon, Steven; Baek, Jong; Rosen, Benjamin; Tar'an, Bunyamin; Millan, Teresa; Zhang, Xudong; et al. (Nature Publishing Group, 2013)
Chickpea (Cicer arietinum) is the second most widely grown legume crop after soybean, accounting for a substantial proportion of human dietary nitrogen intake and playing a crucial role in food security in developing countries. We report the ~738-Mb draft whole genome shotgun sequence of CDC Frontier, a kabuli chickpea variety, which contains an estimated 28,269 genes. Resequencing and analysis of 90 cultivated and wild genotypes from ten countries identifies targets of both breeding-associated genetic sweeps and breeding-associated balancing selection. Candidate genes for disease resistance and agronomic traits are highlighted, including traits that distinguish the two main market classes of cultivated chickpea—desi and kabuli. These data comprise a resource for chickpea improvement through molecular breeding and provide insights into both genome diversity and domestication.